MAIN PROBLEMS OF MOULDING OF SILUMINS. WAYS OF SOLUTION - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия)
The main problems of silumin’ moulding are connected with insufficient modifying of casting structure, their considerable inclination to gas porosity, difficult to remove nonmetallic inclusions and these features are shown in the article. Protection of liquid silumin from influence of the air atmosphere; use of crucibles from aluminum oxide; refinement of fusion from nonmetallic inclusions and application of the accelerated hydrogen hardening of castings were used to solve these problems, as it is shown in the article.